Lubricin is expressed in chondrocytes derived from osteoarthritic cartilage encapsulated in poly (ethylene glycol) diacrylate scaffold - Musumeci, G. (PAGEPress Publications, 2011)
Osteoarthritis (OA) is characterized by degenerative changes within joints that involved quantitative and/or qualitative alterations of cartilage and synovial fluid lubricin, a mucinous glycoprotein secreted by synovial fibroblasts and chondrocytes. Modern therapeutic methods, including tissue-engineering techniques, have been used to treat mechanical damage of the articular cartilage but to date there is no specific and effective treatment. This study aimed at investigating lubricin immunohistochemical expression in cartilage explant from normal and OA patients and in cartilage constructions formed by Poly (ethylene glycol) (PEG) based hydrogels (PEG-DA) encapsulated OA chondrocytes. The expression levels of lubricin were studied by immunohistochemistry: i) in tissue explanted from OA and normal human cartilage; ii) in chondrocytes encapsulated in hydrogel PEGDA from OA and normal human cartilage. Moreover, immunocytochemical and western blot analysis were performed in monolayer cells from OA and normal cartilage. The results showed an increased expression of lubricin in explanted tissue and in monolayer cells from normal cartilage, and a decreased expression of lubricin in OA cartilage. The chondrocytes from OA cartilage after 5 weeks of culture in hydrogels (PEGDA) showed an increased expression of lubricin compared with the control cartilage. The present study demonstrated that OA chondrocytes encapsulated in PEGDA, grown in the scaffold and were able to restore lubricin biosynthesis. Thus our results suggest the possibility of applying autologous cell transplantation in conjunction with scaffold materials for repairing cartilage lesions in patients with OA to reduce at least the progression of the disease.